Analisis Pesebaran Akar Tanaman Kelapa Sawit (Elaeis guineensis Jacq.) pada Jarak dan Kedalaman serta Unsur Hara NPK yang Berbeda - Bakri, Bakri; Siagian, Praktis E. (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Bakri, B., Siagian, P. E. 2023. Analysis of distribution of oil palm plant roots (Elaeis guinneensis Jacq.) at different distances depths and soil N, P, K content. In: Herlinda S. et al. (Eds), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp.172-184). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI)The roots of the oil palm plant grow from the base of the stem and spread to the sides and consist of primary, secondary, tertiary, and quarter roots. NPK is a macro nutrient needed by oil palm plants to grow and produce good production. The purpose of this study was to study the effect of soil NPK nutrients on the distribution patterns of oil palm roots, both primary, secondary and tertiary roots at different soil spacings and depths. This study used a survey method by observing. The data obtained are in the form of distribution of roots, N-Total, Available P, and Potassium which are presented in the form of tables and figures and are discussed in a descriptive way. To determine the relationship between roots and NPK, Pearson Correlation (r) and linear regression tests were carried out. The results showed that the distribution of primary, secondary, and tertiary roots of oil palm plants was higher at a distance of 100 cm and a depth of 0-30 cm and 31-60 cm. the total distribution of primary, secondary, and tertiary roots in plants 1, 2, and 3 based on distance and depth, the highest root distribution was obtained, namely in plant 3 with a depth of 0-30 cm and a distance of 100 cm, namely 7.839 g/dm3. Soil chemical properties in the form of nutrients N and P have a positive correlation with the distribution of oil palm roots.